Comparative study of diesel sorption performance between Chorisia speciosa fibers and a commercial polyurethane foam - Albuquerque,Carla Gonçalves (2021)
ABSTRACT The objective of this work was to evaluate and compare the potential of polyurethane and kapok (Chorisia speciosa) residues as sorbent materials in the treatment of diesel spillage. To determine the sorption capacity, gravimetric tests were performed in static medium at room temperature and at different temperatures (10, 15 and 28 °C) and varying the time of contact between the sorbent material and diesel. It was observed that the sorption process occurs at a high velocity, with saturation point achieved in the first 5 minutes of contact, and the natural fiber presents higher sorption capacity compared to the polyurethane residue due to the low viscosity of diesel oil, that contributes to reduce de entrapment inside the porous foam. It has also been observed that the polyurethane residue exhibits an increase in sorption capacity with time and temperature increase. Scanning electron microscopy (SEM) analysis have shown that the main morphological property involved in smooth oil sorption was the high porosity associated with a small porous diameter. The kapok presented sorption capacity of 37 g/g in equilibrium demonstrating its great potential of application as a sorbent material for the treatment of diesel spillage.